Public Discourse on Import Dependency of Russian Shipbuilding and Its Overcoming During World War I - A. A. Ivanov (Научный диалог, 2025)
This study investigates public opinion in the Russian Empire during World War I regarding the import dependency of the nation’s water transport and shipbuilding sectors, as well as strategies for achieving technological sovereignty. The research examines the underlying causes that led to Russia’s reliance on foreign procurement and the price competitiveness challenges faced by vessels constructed at domestic shipyards. It analyzes publications from leading specialized periodicals of the era, highlighting key positions and opinions expressed in the press by representatives of Russian society. For the first time, this study introduces a range of journalistic texts from Russian engineers, inventors, and sailors addressing these issues into scholarly discourse. It is noted that despite differing approaches, participants in the public debate converged on key issues. Beyond mere criticism, they formulated a comprehensive modernization program for domestic shipbuilding. The relevance of this research is underscored not only by its focus on topics previously overlooked in historical scholarship but also by the contemporary state of Russian industry, which, under sanctions, faces similar challenges. The novelty of this study lies in its examination of the import dependency of Russian water transport and shipbuilding through the lens of public discourse.